Gramaticalització i funció discursiva dels verbs de percepció - Marín Jordà, Maria Josep (Caplletra. Revista Internacional de Filologia, 2005)
This paper deals with Catalan perception verbs reanalyzed as discourse markers. The study focuses on the forms «aviam, a veure» (derived from veure ‘to see’), «miri» (from mirar ‘to look’), and «escolti» (from escoltar ‘to listen’), in a corpus of electoral debate. The research shows the interrelation between semantic and morphosyntactic features, on the one hand, and between these formal aspects and the pragmatic functions of the markers, on the other hand. The analysis highlights that perception verbs as discourse markers indicate power and politeness relationships among the participants in politicaldebates, and this use is closely related to their origin as (active/passive, visual/auditory) verbs of perception and the different degree of grammaticalization that they exhibit asdiscourse markers.